Analisis SWOT Faktor Penyebab Penurunan Jumlah Peserta Didik Lembaga PAUD di Kabupaten Bogor - Erna Kusumawati (Tarbiatuna: Journal of Islamic Education Studies, 2022)
This study aims to analyze the SWOT factors that cause the decline in students in Early Childhood Education (PAUD). This research is a case study in one TKQ in Bogor Regency using a qualitative descriptive method through interviews and field observations. The results showed that the factors that caused the decrease in students in one PAUD institution were starting with the identification of strengths, weaknesses, opportunities, and challenges. TKQ Education has not prioritized strengths and minimized weaknesses and has not been able to take advantage of opportunities to be better. TKQ Education has not been able to maintain several quality components such as coordination, cooperation, consumers, commitment and involvement of all elements of the school and community to improve the quality of TKQ Education together. Keywords: SWOT analysis, causal factors, reduced students